Synthesis of poly (glycidyl methacrylate) through reversible addition-fragmentation chain transfer (RAFT) polymerization - Aashwiny Chandrasegar, 1995- , author 616693; 546260 Khairil Juhanni Abd. Karim, supervisor; Fakulti Sains 8004 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2018